KOMPOSISI PROKSIMAT RUMPUT LAUT HIJAU ASAL PANTAI TELUK SEPANG KOTA BENGKULU - Nurlaila Ervina Herliany (Universitas Halu Oleo, 2022)
Green seaweesd has a high abundance in Indonesia, including on Teluk Sepang Beach, Bengkulu City. However, until now, there is no information about the composition of the green seaweeds from Teluk Sepang Beach, Bengkulu City. This research was held to determine proximate composition of dry green seaweeds from Teluk Sepang Beach, Bengkulu City. This research was conducted from November 2021-April 2022. Green seaweeds was taken from Teluk Sepang Beach. Sample preparation and moisture content were carried out at the Fisheries Laboratory, and for other proximate analyzes (ash content, protein content, fat content, carbohydrate content, and crude fiber) were carried out at the Animal Husbandry Laboratory. The methode of moisture content, ash content, fat content, protein content, and crude fiber refer to the AOAC (2016), while the carbohydrate content based on by difference which refers to FAO (2002). From 6 species of green seaweeds, the largest composition is carbohydrates (27.44±2.80%-50.49±3.27%) and ash (12.23±0.44%-41.22±0.06%) which plays an important role in the intake of nutrients for humans and the food industry. The protein content (0.50±0.03%-4.81±0.17%) and crude fat (0.40±0.00%-2.40±0.30%) is relatively low, so green seaweeds is good for health. Crude fiber (1.37±0.00%-6.26±0.10%.) is relatively low, but not different from several existing studies.Keywords:green seaweeds, proximate composition, Teluk Sepang Beach